Publisher Correction: c-Maf controls immune responses by regulating disease-specific gene networks and repressing IL-2 in CD4 + T cells - Gabryšová, Leona; Alvarez-Martinez, Marisol; Luisier, Raphaëlle; Cox, Luke S.; Sodenkamp, Jan; Hosking, Caroline; Pérez-Mazliah, Damián; Whicher, Charlotte; Kannan, Yashaswini; Potempa, Krzysztof; Wu, Xuemei; Bhaw, Leena; et al. (Nature immunology, 2019)
In the version of this article initially published, the Supplementary Data file was an incorrect version. The correct version is now provided. The error has been corrected in the HTML and PDF version of the article.
Gesehen am 27.04.2020